Courts and prisons: practices of criminal imprisonment in the London metropolis, 1750-1845 - Mehta, K (2021)
This dissertation looks at the development of criminal imprisonment and the evolution of prison systems in the London metropolis between the mid-eighteenth and mid-nineteenth centuries. It combines a study of the processes through which individuals came to be incarcerated with an examination into the regulation and experience of confinement with the aim of explaining the functions that London’s prisons came to serve and the forms that they assumed.